(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to evaluate the response of arugula (Eruca sativa) seeds and early seedlings to salinity stress induced by sodium chloride (NaCl) in a pot experiment conducted under semi-controlled environmental conditions in Al-Zawiya, Libya. Salinity is one of the major abiotic constraints limiting successful seed germination and early plant establishment in arid and semi-arid regions. The experiment was laid out in a completely randomized design (CRD) with five salinity levels (0, 50, 100, 150, 200 mM NaCl) and four replications per treatment. Germination percentage, mean germination time (MGT), germination speed index, and several early seedling growth traits (radicle length, shoot length, fresh and dry seedling weight) were recorded, and a seedling vigor index was calculated. Data were subjected to analysis of variance at α = 0.05. The results showed that increasing NaCl concentration caused a significant and progressive reduction in germination percentage and germination speed, accompanied by an increase in MGT, with the most pronounced inhibition observed at 150 and 200 mM NaCl. Early seedling growth was also adversely affected, as indicated by marked reductions in radicle and shoot lengths, fresh and dry biomass, and seedling vigor index under the higher salinity levels, whereas the decline at 50 and 100 mM was less severe. These findings indicate that the germination and early seedling stages of E. sativa are sensitive to elevated salinity, although a relatively acceptable performance can be maintained under low to moderate salinity levels. The study highlights the usefulness of germination and vigor indices as early screening tools for assessing salt stress tolerance and for defining more suitable conditions for arugula cultivation in salt-affected environments.